Exposing Textual Corruption: Community as a Stabilizing Aspect in the Circulation of the New Testament Writings during the Greco-Roman Era. (December 2020) - Mitchell, Timothy
Because few manuscripts of the NT writings are preserved from the first three centuries of the Christian era, scholars have debated the extent that modern critical editions of the NT reflect the text in circulation during these early centuries. In order to answer this question, this article will set out the evidence for ancient publication through community transmission. It will consider examples from Cicero, Martial, Quintilian, Pliny the Younger and Galen. These authors reveal that they preferred social networks rather than commercial dealers to circulate their writings. These same communities that copied and distributed an author's works inadvertently created an environment in which significant alterations and plagiarizing of these same writings became known. Matthew D.C. Larsen, who has recently approached the same problem addressed in this article by examining ancient publication conventions, is engaged with throughout. The conclusions drawn here press hard against Larsen's assertions.